Psychometric Validation of a Measure Assessing Functional Limitations of Students With Disabilities: An Adaptation of the World Health Organization Disability Assessment Schedule 2.0. (October 2021) - Umucu, Emre; Schlegelmilch, Amanda; Brinck, Emily; Hartman, Ellie; Iwanaga, Kanako; Estala, Veronica; Roskowski, Matt; Lee, Beatrice; Anderson, Catherine A.; N. Tansey, Timothy
The 12-item World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) has been used to assess functional impairments in various disability populations and has been shown to be applicable to the youth population. The purpose of the study was to evaluate the psychometric properties of the World Health Organization Disability Assessment Schedule II–Youth Version (WHODAS-Y). Results of the study revealed a two-factor solution, including the socio-cognitive index and self-care index. The WHODAS-Y measurement appears to be a reliable and valid measure of function impairment in transition-age youth with disabilities in a community setting. This assessment tool can be integrated in vocational rehabilitation practices and guide rehabilitation counselors in identifying needs and facilitators related to education and employment-related services, as well as understanding health care needs in youth with disabilities.